Pakistan : Sixth Review Under the Extended Arrangement and Modification of Performance Criteria-Staff Report; Press Release; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report ;, 2015)
EXECUTIVE SUMMARY Extended Arrangement under the Extended Fund Facility (EFF): A 36 month, SDR 4,393 million (425 percent of quota) Extended Arrangement under the EFF was approved by the Executive Board on September 4, 2013 and the fourth and fifth reviews were completed on December 17, 2014, for a total disbursement of SDR 2,160 million. The sixth tranche amounting to SDR 360 million will be available upon the completion of this review. Status of the program: All end-December 2014 quantitative performance criteria (PCs) were observed, as well as the indicative target on cash transfers under the Benazir Income Support program (BISP). Although the indicative target on federal tax revenues was missed, the authorities have taken actions to address the shortfall and are on track to meet the end-March 2015 indicative target. The end-December 2014 structural benchmark (SB) on amendments to the relevant tax laws and submission of the Anti- Money Laundering Act (AMLA) was met, as were the end-February SBs on enhancing internal operations and risk management of the State Bank of Pakistan (SBP) and improving monetary policy operations. Adjustments to the end-March PCs on NIR and NDA are proposed to reflect higher reserves accumulation by the SBP and new end- June PCs and four new SBs are proposed. Key issues: Discussions focused on: (i) saving the windfall from falling oil prices to strengthen buffers?including foreign exchange reserves and the fiscal stance?against adverse shocks; (ii) preventing a further loss of export competitiveness; (iii) reducing electricity subsidies; (iv) introducing compensatory measures to cover the revenue shortfall; (v) steps to broaden the tax base and improve tax administration; (vi) progress on safeguarding financial stability and expanding credit growth; (vii) enhancing structural reforms in the energy sector, central bank independence, anti-money laundering framework, public debt management, trade, and the business climate to unlock Pakistan's long-term growth potential. The mission retained its growth projection at 4.3 percent, but lowered inflation forecast to 5.5 percent for FY2014/15. Risks are balanced with downside risks due to political uncertainties and security challenges, and upside risks from further falls in oil prices. Outreach activities included a press release, press conference (held in Dubai) and bilateral interviews with journalists.